Potencjał konkurencyjny rolnictwa polskiego w Europie - Maciejewski, Krzysztof (The Competitive Potential of Polish Agriculture in Europe, 2005)
The ability to compete on the European food market is the main economic challenge facing agriculture. Therefore, the study aims at estimating the competitive potential of Polish agriculture in terms of production factors, in comparison with both EU member states and the other European countries.Polish agriculture is characterized by an average land supply, a comparatively good supply of fixed production assets, and excessive labor intensity. Working capital participation is relatively low, which means that increasing it gives scope for a significant rise in the productivity of agriculture. Improving the relation between labor and working capital should become the main direction of any measures taken to increase the competitiveness of Polish farms.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 50-54